Increasing the Reading Interest of Elementary School Students - Vindi Septianingrum; Agrissto Bintang Aji Pradana; Anisa Vigitm (Prosiding University Research Colloquium, 2021)
Reading has an important social role in human life. Reading is not only a necessity forstudents, but also the needs of everyone. Through reading, knowledge can be obtained. Inessence, reading is a bridge to understanding how big the world is. However, in the 21stcentury, it is not the ability to read students, but the lack of interest in reading, be ittextbooks or other books. This is due to the students' lack of understanding of the textsthey read, lack of vocabulary mastery including not understanding how to read well inaccordance with the objectives to be achieved. This article aims to identify ways to increaseelementary students' reading interest. The benefits of this article are knowing theimportance of increasing reading interest, understanding the functions and benefits ofreading, as well as the factors that hinder students' reading interest, along with the roleof parents, teachers, librarians, and the government.